2002
DOI: 10.1021/jf011697q
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Quercetin by Salivary Components. Quercetin-Dependent Reduction of Salivary Nitrite under Acidic Conditions Producing Nitric Oxide

Abstract: Under acidic conditions, nitrite is protonated to nitrous acid (pK(a) = 3.2-3.4) that can be transformed into nitric oxide by self-decomposition and reduction. When sodium nitrite was mixed with quercetin at pH 1-2, quercetin was oxidized producing nitric oxide. In addition to quercetin, kaempferol and quercetin 4'-glucoside were also oxidized by nitrous acid, but oxidation of apigenin, luteolin, and rutin was slow compared to oxidation of the above flavonols. These results suggested that flavonols, which have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 29 publications
3
71
0
Order By: Relevance
“…The resulting spectrum is shown in line 3. The formation of the o-semiquinone radical, corresponding to the one-electron oxidation of the parent phenol is in accordance with results by others, showing the formation of chlorogenic and quercetin radicals upon reaction with acidic nitrite [18,19].…”
Section: μM (Line 4)supporting
confidence: 91%
See 2 more Smart Citations
“…The resulting spectrum is shown in line 3. The formation of the o-semiquinone radical, corresponding to the one-electron oxidation of the parent phenol is in accordance with results by others, showing the formation of chlorogenic and quercetin radicals upon reaction with acidic nitrite [18,19].…”
Section: μM (Line 4)supporting
confidence: 91%
“…Therefore, these compounds are likely candidates to undergo a redox reaction with nitrite during digestion, yielding U NO. Accordingly, chlorogenic acid and quercetin (phenolics exhibiting a catechol moiety) were shown to enhance the production of U NO from nitrite at acidic pH [18,19]. On the other hand, ascorbic acid, a compound that exhibits a low redox potential, and actively secreted in the stomach, has also been shown to be an efficient one-electron reductant of nitrite [42,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that crocin in foods can reduce salivary nitrite to NO in the stomach. It has been reported that some kinds of polyphenols in foods can reduce salivary nitrite to NO in the stomach (Takahama et al, 2002(Takahama et al, , 2010aPeri et al, 2005), and the function of NO generated in the stomach has been discussed from the viewpoint of increases in various activities of the length range from 400 to 600 nm (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…In the stomach, nitrite is protonated producing nitrous acid (pKa = 3.3), an oxidizing and nitrosating agent, to react with food components. It is well known that nitrous acid can transform amines into carcinogenic compounds nitrosoamines [10], and it has been reported that phenolic compounds can reduce nitrous acid to a functional compound nitric oxide ( • NO) [11,12]. The functions of • NO produced in the gastric lumen include the increase in gastric mucosal blood flow, the increase in gastric mucus thickness, and the relaxation of gastric smooth muscle [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%